Modeling Migration from the EU Candidate and Potential Candidate Countries to the EU member states - Bucevska, Vesna (Varazdin Development and Entrepreneurship Agency, Varazdin, Croatia University North, Koprivnica, Croatia, 2016)
The EU candidate and potential candidate countries have a long history of economic emigration to the EU member states. However, the recent influx of refugees from North Africa, the Middle East and South Asia to Europe has raised not only the political, but also traditional economic concerns of large immigration flows. In light of the recent migration developments and the increased migration fear index among the EU member states, the purpose of our paper is to answer the question if the fear of labour migration from the EU candidate and potential candidate countries to the EU member states is justified or not. In order to achieve this objective, we examine a number of determinants of migration from the EU candidate and potential candidate countries to the EU member countries and specify and estimate an extended gravity model of migration, based on panel data analysis, for six EU candidate and potential candidate countries (Albania, Bosnia and Herzegovina, Croatia , Macedonia, Serbia and Turkey) and EU-27 member states in the period 2001-2014. Our results indicate that the difference in income level between the EU-27 and EU candidate and potential candidate countries, measured as real GDP per capita, the gross average monthly wages in the EU candidate and potential candidate countries and the stock of the EU candidate and potential candidate countries’ nationals residing in the EU-27 member states as a share in the total population of the countries of origin are the main determinants of migration from the EU candidate and potential candidate countries to the EU-27. One of the most important finding of our analysis is that the achieved progress of the EU candidate and potential countries on their way towards full EU would have a positive, but only marginal significant impact on the emigration from these countries to the EU member states.
Keywords: EU candidate countries, EU potential candidate countries, gravity model, international migration, panel data